Jenis-Jenis Jamur yang Diisolasi dari Daun Tanaman Semangka (Citrullus vulgaris Schard.) Bergejala Sakit di Desa Rasau Jaya 1 - Mukarlina, Desi Lestari, Rahmawati, (Jurnal Protobiont, 2018)
Watermelon plant (Citrullus vulgaris Schard.) is one of horticulture plants in Rasau Jaya 1 village, Kubu Raya regency, West Borneo. The symptomof the dignose sick watermelon is first found on its leaf. The objective of this research is to find types of fungi that are isolated from the diagnose sick leaf of watermelon (C.vulgaris Schard.) found in Rasau Jaya 1 village. This research took place from August until November 2017 in microbiology laboratorium, faculty of Matematika dan Ilmu Pengetahuan Alam, Tanjungpura University, Pontianak. The isolated method used in this research is direct platting and dilution platting, and also indetification of fungi based on macromorphological and micromorphological characters. This research concludes that there are three types of symptoms of the diagnose sick leaf of watermelon, brownish black spotting, withering yellow and yellow spots. It is also found that there are eight types of fungi which are isolated from the diagnose sick leaf of watermelon fungi from the family of Aspergillus sp.(Dl1) species, Colletotrichum sp.(DI2), Fusarium sp.(Dl3), Fusarium oxsyporum (Dl4), Humicola sp.(Dl5), Macrophomoina sp.(Dl6), Penicillium sp.(Dl7), and Pythium sp.(Dl8).